AGREEMENT OF CAPILLARY-OBTAINED ACYLATED GHRELIN, ACTIVE GLP-1, GLUCAGON, INSULIN AND LEPTIN WITH THEIR VENOUS EQUIVALENTS. Issue 17 (24th October 2013) - Green, BP; Gonzalez, JT; Thomas, K; Dodd-Reynolds, CJ; Bryans, J; Stevenson, E; Rumbold, PLS
Abstract : The purpose of the present study was to examine whether the expression of capillary-derived appetite peptides accurately reflects concentrations of their venous equivalents. Fingertip capillary (2×0.3 mL) and venous blood samples (2×4 mL) were collected simultaneously from 19 healthy adult volunteers [mean age 24.1 (SD 5.7) years, body mass 73.7 (SD 10.9) kg;], for determination of acylated ghrelin, GLP-17–36, glucagon, insulin and leptin. Samples were obtained at baseline (t=0 min) and at 30, 60, 90 and 120 min following consumption of a standardised breakfast. Bland-Altman plots were constructed with their 95% limits of agreement and confidence intervals. All analysis was computed using time-averaged area under the curve data (AUC). Where data were heteroscedastic, data were log transformed and reported as ratio limits of agreement (LOA). With the exception of acylated ghrelin ( r 2 =0.51), venous and capillary blood samples displayed strong correlations between all hormonal peptides ( r 2 ≥0.84). GLP-17–36 and glucagon illustrated no systematic difference between capillary and venous blood samples (0.44±0.63 and −0.19±7.63 pg·mL −1, respectively). Capillary leptin, acylated ghrelin and insulin, on average, underestimated their venous equivalents. Mean log transformed ratio LOA for leptin, insulin and acylated ghrelin were 0.89 (1.19), 0.82 (1.79) and 0.44 (3.12), respectively. Fingertip capillary blood sampling appears appropriate in appetite-related research. Further research is warranted to clarify the acceptability of capillary sampling in lieu of venous blood sampling for the determination appetite peptides.